TiN-Mediated Multi-Level Negative Photoconductance of the ZrO2 Breakdown Path - Zhou, Yu (2017)
We present new evidence that the non-volatile negative photoconductivity (NPC) response of the ZrO2 breakdown path can be suppressed or tuned to different levels by repeated application of a positive voltage-bias on the TiN electrode prior to light exposure. A negative voltage-bias does not produce such a tuning effect but can restore the NPC response suppressed by the positive voltage-bias before a re-breakdown step. In samples with a non-metal (Si) electrode, the NPC tuning effect is absent indicating that a positively biased TiN electrode is needed to produce the tuning effect. We hypothesize that a positive voltage may induce the migration of Ti ions into the vacancy sites in the breakdown path. This then prevents the photo-assisted recombination of the interstitial-vacancy defect pairs, leading to a modulated NPC response. A negative voltage-bias expels the Ti ions back to the electrode and restores the NPC response.